Spatial analysis of the conflicts of urban treatment of the City of Rio Tinto - PB (Research, Society and Development, 2021)
Urbanization causes the occupation of cities to occur in a disorderly manner, representing significant physical changes in nature, and afforestation is a tool to minimize such urban impacts. To analyze afforestation, it is essential to use geographic data obtained through topographic measurements, remote sensing techniques, GPS receivers, etc. Through geoprocessing techniques it is possible to map different situations such as phytosanitary problems, conflicts with electricity networks, signaling, or any type of characters, which assumes a fundamental role in the management of afforestation. This work consisted of registering the conflicts of the afforestation of the city of Rio Tinto - PB and mapping them with the techniques of Geoprocessing. The study was carried out from November 2016 to July 2018. variables analyzed were: location, surroundings, interferences, dimensions, balance, actions and mapping. A total of 931 individuals were cataloged. . In general, the trees are within the recommended standards with regard to electrical wiring, stem and crown balance and dimensions, requiring some management actions. The recommended actions for a better use of the services provided by the trees need to be decided based on prior planning. With the expansion of the city, new forms of interventions will be needed in the future, in order to minimize the impacts.